From noose to needle: capital punishment and the late liberal state - Kaufman-Osborn, Timothy V. (Law, meaning, and violence, 2002)
What is a death sentence? -- John Locke's noose -- The metaphysics of the hangman -- Silencing the voice of pain -- "Womanhood unsexed on the gallows" -- Needling the sovereign.